Prevalence and associated factors of proliferative diabetic retinopathy among adult diabetic patients in Northwest Ethiopia, 2023: A cross-sectional multicenter study. - Abebech Fikade Shumye; Mebratu Mulusew Tegegne; Biruk Lelisa Eticha; Matiyas Mamo Bekele; Asamere Tsegaw Woredekal; Lakew Asmare (PLoS ONE)
Background Proliferative diabetic retinopathy is one of the advanced complications of diabetic retinopathy. If left untreated, almost all eyes could lose a significant portion of their vision within four months. There is limited evidence regarding the magnitude of proliferative diabetic retinopathy and associated factors in the study setting and also in Ethiopia. Purpose To determine the magnitude and associated factors of proliferative diabetic retinopathy among adult diabetic patients attending Specialized Comprehensive Hospital-Diabetic Care Clinics in Northwest Ethiopia, 2023. Methods A multicenter, hospital-based, cross-sectional study was conducted on 1219 adult diabetic patients selected by systematic random sampling technique. Data were collected through an in-person interview and physical examination. The Statistical Package for Social Science Version 20 was used to analyze the data. Logistic regression methods were used to test the association between predisposing factors and proliferative diabetic retinopathy. The adjusted odds ratio with a 95% confidence interval was used to determine the strength of association. Results The prevalence of proliferative diabetic retinopathy was 3.1% (95% CI: 2.10%-4.10%). Hypertension (AOR = 4.35 (95% CI: 1.87-10.12)), peripheral neuropathy (AOR = 3.87 (95% CI: 1.57-9.54)), nephropathy (AOR = 2.58 (95% CI: 1.13-5.87)), ≥10 years duration of diabetes mellitus (AOR = 5.30 (95% CI: 2.32-12.14)), insulin use (AOR = 3.07 (95% CI: 1.08-8.68)), and poor adherence to diabetes mellitus medications (AOR = 3.77 (95% CI: 1.64-8.64)) were confirmed to have statistically significant association with proliferative diabetic retinopathy. Conclusion The prevalence of proliferative diabetic retinopathy among adult diabetic patients in the diabetes clinic was higher than the global study. Hypertension, peripheral neuropathy, nephropathy, ≥10 year's duration of diabetic mellitus, insulin use and poor adherence to diabetes mellitus medications were among the factors significantly associated with proliferative diabetic retinopathy.